From social security to state-sanctioned insecurity: How welfare reform mimics the commodification of labour through greater state intervention. Issue 3 (3rd July 2021) - Koch, Insa; Reeves, Aaron
Abstract: Policymakers seeking to reform social security systems have frequently confronted a central tension: how to reconcile welfare retrenchment with the political challenges of implementing unpopular reforms. One way in which policymakers have responded to this tension is by repurposing existing institutions to serve new ends. We investigate the system of Universal Credit (UC) in the United Kingdom as an example of conversion. UC expands the reach of 'active citizenship' policies to a much larger population than ever before. However, far from producing uniform outcomes, UC's implementation has been marked by chaos and ultimately failure for individuals and communities. We argue that UC exemplifies a broader shift from social security to state-sanctioned social insecurity as policy reforms come to mimic the insecurities and risks commonly associated with the market.